Authority Architecture And Architecture Criticism - Sana Sati Abbas; suha Hassan Al-Dahui (Iraqi Journal of Architecture and Planning, 1970)
Many ol criticism studies have focused on the concept of aurhority . These studies vary intheir intentions, about the type of authority , according to their theoretical criticism direcrions.Also they varied in their disciplines, from lhe attention to the author, to co,nplete care to the text;eventually they transferred to the reader in thc last decade of the t\\'entieth century .The researchproblem rvas "There is no conrprehensive image about the concept ofauthority in Architectureand specially in Academic architectural criticisnr". This study aims to define the specialty ofauthority in architecture and architectural criticisnr .The research hl,pothesis rvas " the authorityin architecture is convenient have rnultiple resources ,meanings ,and disciplines of enfolding. tt isappear in the text exhibited to criticism through external items expresses the era and the rules ofart. The methodology of the research is based on(theoretical study rvhich defines the theorcticalframework for authority concept in architecture and architectural criticisrn in general andpractical study rvhich investigated a group of academic critics, about the item ofthe framervork.The results obtained are analyzed to reach to the conclusions about the lraqi specialty ofauthorityin architeclure and architectural criticism .Research findings u,as (rhe authority in architectureand criticism is convenient, its resource is the text, includes many meaning. the most lamous isthe creativity . the elfects and the superiority .l he authority emerges in exhibitions, local andinternational competitions, and in the students producls .The authority depends on some means,the most famous are .the designers continuous encouragement .grades gir en . and the explanation.in order to produce products responding to the era , through dealing u,ith rhe design process, andthe context used).